Making the past serve the present: the instrumental use of historical memory by China’s paramount leaders - Kotowski, Matthew (My University, 2024)
Communist Chinese paramount leaders instrumentally use historical memory to secure and then retain their authority as the “core” of the Chinese Communist Party (CPC). The leaders examined include Mao Zedong, Deng Xiaoping, Jiang Zemin, Hu Jintao, and Xi Jinping. Core leadership refers to the political and ideological dominance of an individual leader over the collective leadership within the CPC’s political culture. This authority is not granted with any formal title of leadership but must be earned. Its level of influence can vary and can shift over time as paramount leaders struggle for influence with the collective leadership. A key component for gaining this leadership is crafting and then disseminating a historical narrative which promotes their claim to leadership and subsequently the adoption of their governing philosophy as the party-state’s guiding ideology. I argue that these core leaders wield historical memory to achieve and then maintain this influence. The redefinition of historical memory legitimizes their ascension to supreme power, as well as promoting their governing philosophy as the supreme guide to government and party policy. Employment of historical memory further sustains their power and garners support for their preferred policy positions. To map the shifts in their relative instrumental usage, I employ a Political Discourse Analysis approach to quantify the instrumental uses of historical memory within each leaders’ discourse, relying heavily, although not exclusively, on their Selected Works. This mapping displays the variance over time in the core leader’s relative use of historical memory and allows me to correlate such changes to alterations of their authority as core leaders based on existing scholarship. In addition, I identify four broad categories (Confucian/Traditional, Marxist, Nationalist, and Liberal), to which specific instrumental uses of historical memory by core leaders may be assigned. These categories allow the investigation of the political objectives pursued by the core leaders through the instrumental usage of historical memory. Furthermore, I display the shifts diachronically by leaders in the proportion of each category within their discourse, as well as dissect that usage based upon specific audiences (Party, Domestic, and Foreign). The distinction in their usage offers further evidence for the political intent of such usages within their discourse. By actively shaping and propagating purposefully selective historical memory, Communist Chinese leaders can better secure their position as core leader, promote their ideology, and pursue their policy objectives.
Keywords: Instrumental use of historical memory; Communist China political culture; Political discourse analysis; People's Republic of China paramount leaders; People's Republic of China history; Communist China historical narratives